Fabrication and characterisation of bismuth nanowires - Cornelius, Thomas Walter (2006)
Single- and polycrystalline bismuth nanowires were created by electrochemical deposition in ion track-etched polycarbonate membranes. Wires fabricated potentiostatically possess a strong texture which becomes more pronounced for wires deposited at lower overpotentials, at higher temperatures, and in nanopores of smaller diameters. By applying reverse pulses, wires that are textured can be grown where the texture increases for shorter pulses and higher anodic potentials. Infrared spectroscopic microscopy on single bismuth nanowires reveals an absorption whose onset is blueshifted with decreasing wire diameter. The observed effect may be attributed either to an increase of the direct band gap at the L-point of the Brillouin zone caused by quantum-size effects, or to a blueshift of the plasma frequency produced by surface defects acting as dopants. In addition, electrical resistance of single bismuth nanowires, embdedded in the template, has been measured as a function of both wire crystallinity and temperature. The results demonstrate that finite-size effects affect the wire resistivity which is higher than the bulk value and depends on the mean grain size. Measurements as a function of temperature demonstrate that the charge carrier mobility saturates at low temperatures because of electron scattering at grain boundaries, resulting in a non-monotonic resistance versus temperature behaviour. Further, measurements of the electrical resistance of wire arrays as a function of the magnetic field show a rising magnetoresistance with increasing diameter and growing mean grain size.
Keywords: Hochschulschrift